BIOMEKANIKA PENDARATAN DAN CIDERA OLAHRAGA PADA ATLET BOLA VOLI PUTRI CLUB CIPALIMA KABUPATEN MERANGIN - Nurul Azizah Maysaroh; Adhe Saputra; Iwan Budi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Volleyball is a sport that involves a great deal of jumping and landing. These movements carry a relatively high risk of injury, particularly to the ankles. Improper landing techniques can cause loss of balance and increase the likelihood of injury among athletes. Based on observations of female volleyball athletes from the Cipalima Club in Merangin Regency, it was found that some athletes still employ poor landing techniques, such as insufficient knee bending upon landing, unstable body balance, and uneven body weight distribution. This study aims to analyze the biomechanics of landing and the risk of ankle injury among female volleyball athletes from the Cipalima Club in Merangin Regency. This study employs a quantitative approach using a descriptive method. The subjects of this study are the female volleyball athletes of the Cipalima Club in Merangin Regency. Data collection was conducted through observation and measurement using several instruments, namely the Landing Error Scoring System (LESS) to assess landing technique errors, the Star Excursion Balance Test (SEBT) to measure dynamic balance, and the Ankle Injury Risk Index (AIRI) to determine the level of ankle injury risk among the athletes. The results of the study indicate that some athletes still make errors in their landing technique, characterized by insufficient knee flexibility, unstable body control, and suboptimal balance. These conditions indicate a potential risk of ankle injury. Athletes with better biomechanical landing techniques tend to have a lower risk of injury compared to those with poorer landing techniques. The conclusion of this study indicates that landing biomechanics plays a crucial role in minimizing the risk of sports injuries among female volleyball athletes. Therefore, training that emphasizes proper landing technique, improved balance, and strengthening of the lower extremity muscles is necessary to reduce the risk of injury among athletes.